MENINGKATKAN KESADARAN BERKOPERASI SYARIAH DALAM MEWUJUDKAN IMPLEMENTASI KETANGGUHAN KETAHANAN NASIONAL BIDANG EKONOMI - Ridhuan, Syamsu; Elistia, Elistia; Astuty, Widya (Universitas Esa Unggul, 2019)
Comunity service partners are the National Unity and Political Agencyof the Jakarta Provincial Gevernment. One of the tasks and functions of forming and fostering the National IntegrityÃ‚Â Forum.Members came from representations of 34 ethnic provinces in Indonesia and 3 (three) from ethnic Chinese, Arabic and Indian descendants. The problem faced by partenrs is the desire to improve welfare and empower members to be able to try independently to strengthen economic recilience. But there is no appropriate place to the mobilize and empower the economy to be seen as the right way to achieve the goal.The method of activity is the transfer of knowledge andragogically by : assistance, consultation, socialization and the practice of establishing sharia coopratives jointly between national integrity forum with lecturers and community service implementing students, facilitated by theNational Unity and Political Agency of the Jakarta Provincial Gevernment.Providing tehnical assistance in establishing sharia cooperatives with direct involvement as managers and members of cooperatives.The result of community service is the National Sharia Cooperatuce characrterized by a notary deed of establishment and a cooperative legal entity. Output of scientific articles published in the national journal Abdimas Esa Unggul.Ã‚Â Keywords: Coperatie, recilience, sharia.